EFFECT OF LEMON AROMATHERAPY IN PREGNANT WOMEN ON EMESIS GRAVIDARUM: A LITERATURE REVIEW - Fibriansari, Rizeki Dwi; Hayati, Nurul (Universitas Airlangga, 2023)
Introduction: Pregnancy is a physiological event for a woman and in the first months of pregnancy, there is a feeling of nausea and vomiting (gravidarum emesis). Emesis complaints occur in 60-80% of primigravida and 40-60% of multigravida. Emesis gravidarum if not treated immediately can develop into hyperemesis gravidarum and can result in reduced fluids in the body, thus endangering the health of the mother and the development of the fetus. The purpose of this study is to examine scientific articles which discuss lemon aromatherapy in pregnant women to reduce emesis gravidarum. Methods: The method used in this study is a literature review with data collection techniques using PubMed and Scholar based on inclusion criteria, among others, the intervention in the form of giving lemon aromatherapy, using the quasi-experiment or pre-experimental design or literature review method, using Indonesian and English, published within 10 years (2017-2022). Keywords in the literature review used when searching